2013
DOI: 10.1038/sc.2013.13
|View full text |Cite
|
Sign up to set email alerts
|

Elbow problems in paraplegic spinal cord injured patients: frequency and related risk factors—a preliminary controlled study

Abstract: Study design: Cross-sectional controlled study. Objectives: To evaluate the elbow joint with ultrasound in paraplegic patients, determine the related factors and compare it with healthy controls. Setting: A training and research rehabilitation hospital in Istanbul. Methods: A total of 30 paraplegic patients and 20 healthy controls were included in the study. Patients demographic data, pain in the elbow joint, level and duration of injury, ambulation status, type of wheelchair used, daily duration of wheelchair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 13 publications
1
2
0
Order By: Relevance
“…Similar rates have been reported by Dalyan et al and Pentland et al (35% and 31%,respectively) [21,24]. In other studies, the prevalence is reported as 5-23% [4,20,23]. Elbow pain associated with chronic overuse has been widely studied in the able-bodied population, and its most common pathology is lateral epicondylitis (i.e., tennis elbow) [44] and it occurs in those who frequently perform forceful and repetitive movements [45].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Similar rates have been reported by Dalyan et al and Pentland et al (35% and 31%,respectively) [21,24]. In other studies, the prevalence is reported as 5-23% [4,20,23]. Elbow pain associated with chronic overuse has been widely studied in the able-bodied population, and its most common pathology is lateral epicondylitis (i.e., tennis elbow) [44] and it occurs in those who frequently perform forceful and repetitive movements [45].…”
Section: Discussionsupporting
confidence: 84%
“…Although pathological conditions of the shoulder and wrist joints in individuals with paraplegia who are wheelchair dependent have been extensively studied [3,[13][14][15][16][17][18][19], only a few studies focused on the prevalence of elbow pain and its etiologies [20][21][22]. Several previous studies have focused primarily on the prevalence of wrist pain.…”
Section: Introductionmentioning
confidence: 99%
“…Shoulder problems can be caused by acute injury or chronic pathology, but are most often related to overuse injuries of the rotator cuff (36)(37)(38). Whereas for elbow/wrist problems, the elbow joint is often overused particularly during push-up manoeuvres required for both weight shifts and transfers (39). Both elbow/wrist and shoulder problems can significantly negatively affect a person's health and function; thus, this significant association between elbow/wrist problems and shoulder problems can enable clinicians to identify these injuries earlier, and employ treatment and/or preventive strategies to preserve shoulder and elbow function after SCI.…”
Section: Discussionmentioning
confidence: 99%